2021
DOI: 10.1161/strokeaha.120.029232
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Blood-Based Biomarkers in Ischemic Stroke Prognosis

Abstract: Background and Purpose: Outcome prognostication in ischemic stroke patients remains challenging due to limited predictive properties of existing models. Blood-based biomarkers might provide additional information to established prognostic factors. We intended to identify the most promising prognostic biomarkers in ischemic stroke, their incremental prognostic value, and whether their predictive value differs among etiologies. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 39 publications
2
86
0
Order By: Relevance
“…Studies have suggested that various circulating proteins are directly related to acute ischemic injury or inflammation of the CNS [5][6][7]. Brain tissues that become necrotic after stroke and the associated inflammation may release neuronal or glialspecific proteins into the cerebrospinal fluid and the blood, but their concentration in the peripheral blood is usually extremely low [8]. With advancements in detection technology, such as ultrasensitive immunoassays, these trace biomarkers can now be measured with confidence, potentially assisting in stroke prognosis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that various circulating proteins are directly related to acute ischemic injury or inflammation of the CNS [5][6][7]. Brain tissues that become necrotic after stroke and the associated inflammation may release neuronal or glialspecific proteins into the cerebrospinal fluid and the blood, but their concentration in the peripheral blood is usually extremely low [8]. With advancements in detection technology, such as ultrasensitive immunoassays, these trace biomarkers can now be measured with confidence, potentially assisting in stroke prognosis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The final phase of stroke is the chronic stage that sets after approximately six weeks from the initial event. The BBB permeability is restored to almost the same level as before, even if the neuroinflammation response is still present, as cytokines levels are still raised above normal [8][9][10][11] (Figure 2). The purpose of this article is to review the current biomarkers related to atherothrombotic stroke, focusing on their roles as a risk factor, detection marker, and prognostic predictor, and therapeutic targets.…”
Section: Introductionmentioning
confidence: 64%
“…These immune cells exacerbate the injury by releasing additional inflammatory factors, such as ROS, MMP-9, and neutrophil elastase, which are prominent effectors of BBB disruption [17]. It also has been shown that most AIS patients course some degree of immune dysregulation; however, when these mechanisms are overstimulated worsen short and long-term clinical outcomes are expected [18][19][20].…”
Section: Discussionmentioning
confidence: 99%